Korelasi Antara Pengetahuan dan Perilaku Masyarakat di Desa Sukabakti Kabupaten Bekasi Terhadap Pengobatan Mandiri Penyakit Maag - Nurhayati, Nunung; Julianti, Eri (Jurnal Ilmiah Kesehatan, 2023)
Gastritis is a digestive tract problem that is most often found in everyday life and a health disorder that is often found in clinics because the diagnosis is only based on clinical symptoms. The purpose of the researcher is to conduct direct research on the people of Sukabakti Village, Tambelang District, Bekasi Regency, who are taken as research subjects. These knowledge questions were grouped into 15 questionnaires which were categorized into 3 levels, for the high category with a value of 100-76%, moderate/enough 75-56%, less/low <56%. The behavioral questionnaire category consisted of 15 questionnaires grouped into positive with a score of more than 15 and negative with a score of less than 15. The number of samples in this study was 100 using purposive sampling, while there were 5,300 people in Sukabakti Village. This research uses field research which is carried out systematically by collecting existing data in the field. This researcher was analyzed using Chi-Square with SPSS version 25. The results of the data on the most respondents aged 25-34 were (26%), the highest education was elementary school (49%). The average respondent's knowledge with a score of 83%, positive respondent behavior 81%. The Chi-square test shows a significant value of 0.000 <0.05, meaning that there is a relationship between the level of self-medication knowledge of ulcers in the community in Sukabakti Village, Tambelang District, Bekasi Regency.